PENGARUH PARTISIPASI ANGGARAN, PENEKANAN ANGGARAN, ASIMETRI INFORMASI, KOMITMEN ORGANISASI, KEJELASAN SASARAN ANGGARAN, DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP BUDGETARY SLACK (STUDI EMPIRIS PADA ORGANISASI PERANGKAT DAERAH DI KABUPATEN JEPARA) - Amelia Pratiwi, Cindy (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2023)
This study aims to determine the effect of budget participation, budget emphasis, information asymmetry, organizational commitment, clarity of budget targets, and environmental uncertainty on budgetary slack. This research is included in quantitative research using primary data. The population in the study amounted to 10,007 people (Regional Organizations (OPD) Jepara Regency, 2021). The sampling technique used purposive sampling technique with 100 respondents. The results of this study indicate that budget participation has no effect on Budgetary Slack. Budgetary emphasis has a significant positive effect on Budgetary Slack. Information asymmetry has no effect on Budgetary Slack. Organizational commitment has a significant negative effect on Budgetary Slack. Clarity of Budget Targets has a significant positive effect on Budgetary Slack and environmental uncertainty has a significant positive effect on significant positive on Budgetary Slack